THE ROLE OF THE CITIES IN THE NATION CONSTRUCTION - Ferrero Micó, Remedios (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
One of the most important questions raised in the crucial period 1810-1812 was legitimacy and governability of the cities. Who governs and on behalf of who? as it was stated by F.X. Guerra. The cities retook the control of their sovereignty and fronted the nationalist demands. The king being absent, the cities decided that their sovereignty should return to the people from where it came from. In view of the situation of Spain, the American world was divided as in the metropolis. The break-up of the Junta Central and the constitution of the controversial Council of Regency touched the American society and that restlessness was reflected in the town councils. The cities, as central axis, and the towns, around which the activities of the neighbors are organized, constituted a political reference. But what was understood by towns? The cities with town council or the capital cities that attributed themselves that right?